PERAN HEPSIDIN SEBAGAI REGULATOR METABOLISME BESI - Purwanto, Diana S (Jurnal Biomedik : JBM, 2012)
Abstract: Hepcidin is an antimicrobial peptide hormone synthesized in the liver, distributed in plasma, and excreted in urine. Besides that, it is a main regulator of iron metabolism. Hepcidin belongs to the type II acute phase proteins and its synthesis is mainly controlled by the activity of bone marrow erythropoiesis, iron storage, and inflammatory processes in the body. It acts as a negative regulator of intestinal iron absorption and removal by macrophages and hepatocytes. Hepcidin, bound to the ferroportin receptor, causes the internalization and degradation of ferroportin which leads to iron retention in enterocytes, macrophages, and hepatocytes. Hepcidin synthesis is stimulated by a high transferrin saturation (iron excess and inflammation), and is inhibited by a low transferin saturation (anemia and hypoxia). Its excess is a major contributor to the pathogenesis of anemia in inflammatory processes, as well as its deficiency being responsible for most cases of hereditary hemochromatosis.Keywords: hepcidin, antimicrobial peptide, iron, inflamation, hemochromatosis.Abstrak: Hepsidin merupakan hormon peptida antimikroba yang disintesis oleh hepar, didistribusikan dalam plasma dan diekskresi melalui urin. Hepsidin menjadi regulator utama bagi metabolisme zat besi. Sintesis hepsidin terutama dikontrol oleh aktivitas eritropoiesis sumsum tulang, penyimpanan zat besi, dan adanya inflamasi dalam tubuh; juga telah dibuktikan merupakan protein fase akut tipe II. Hepsidin berperan sebagai regulator negatif absorpsi besi usus dan pelepasan besi oleh makrofag dan hepatosit. Hepsidin yang terikat pada reseptor feroportin menyebabkan internalisasi dan degradasi feroportin dan retensi besi dalam enterosit, makrofag dan hepatosit. Sintesis hepsidin dirangsang ketika saturasi transferin tinggi (saat terdapat kelebihan besi dan inflamasi), sebaliknya sintesis hepsidin dihambat ketika saturasi transferin rendah (pada anemia dan hipoksia). Kelebihan hepsidin merupakan kontributor utama terhadap patogenesis anemia inflamasi, dan kekurangan hepsidin bertanggung jawab pada sebagian besar kasus hemochromatosis herediter.Kata kunci: hepsidin, peptida antimikroba, besi, inflamasi, hemokromatosis.